Effect of a somatostatin analogue on gastric motor and sensory functions in healthy humans. Issue 11 (21st October 2003) - Foxx-Orenstein, A; Camilleri, M; Stephens, D; Burton, D
Abstract : Background: Pharmacological approaches to alter satiation may have an impact on functional upper gastrointestinal disorders and potentially change food intake in obesity. Aim: Our aim was to compare the effects of two doses of octreotide and placebo on postprandial symptoms, gastric accommodation, and gastric emptying using validated non-invasive techniques. Methods: In a randomised, parallel group, two dose, double blind, placebo controlled study, 39 healthy participants (13 per group) were randomised to 30 or 100 µg octreotide or placebo, administered subcutaneously, 30 minutes before each study. Studies were performed on three separate days and included scintigraphic gastric emptying of solids and liquids, 99m Tc SPECT imaging to measure fasting stomach volume and gastric accommodation following a 300 ml Ensure meal, and a standardised nutrient drink test to measure maximum tolerated volume and postprandial symptoms. Results: Relative to placebo, both doses of octreotide delayed gastric emptying of solids (not liquids), increased fasting gastric volume, reduced the change in gastric volume post meal, and decreased the sensation of fullness after a satiating meal. Conclusion: The somatostatin analogue octreotide significantly alters human gastric functions, including inhibition of the normal reflex responses of gastric volume increase and emptying of the meal. These pharmacological effects suggest studies of the medication in disorders of satiation, including obesity and dyspepsia, are warranted.